Coconut Oil Heat Capacity - Bardan Bulaka; Syarifuddin Syarifuddin; Eko Harianto (IKIP Mataram, 2021)
Heat is energy transferred between a system and its surroundings due to the temperature difference that exists between them. Phase changes of coconut oil can be seen at temperatures between 20°C–100°C. To calculate the incoming heat using the equation Q = m.c.ΔT. Where Q in the experiment is calculated by the equation Q = V.I.t. So to calculate the specific heat of heat (c) = Q/(m.ΔT). The heat capacity is obtained from the equation C = m.c. The method in this practicum is used heater with AC current. The heater used has a voltage of 220 Volts, with a power of 350 Volts. Because the heating voltage is too large, a variable ac (variac) is used to lower the voltage. The voltage used is 20 volts. The material used is coconut oil which is labeled